A New Method to Model the Thickness Change of a Commercial Pouch Cell during Discharge. Issue 8 (1st January 2016) - Rieger, Bernhard; Erhard, Simon V.; Rumpf, Katharina; Jossen, Andreas
Abstract : The displacement of a commercial pouch cell during discharge is modeled and validated using a thermally coupled physico-chemical model. To achieve high accuracy, we derive five different profiles for a concentration-dependent volume change in the graphite particles from literature. Based on the particle volume changes in the positive and the negative electrodes, the pouch cell displacement is calculated and compared to experimental data for all derived graphite characteristics at a low current discharge scenario. One graphite profile is chosen for investigating the pouch cell displacement at higher discharge rates. The thermal expansion of the pouch cell is determined by pulse excitation measurements to distinguish between thermal displacement and intercalation displacement. Our model is capable of describing the cell potential, the cell temperature and the cell displacement with high accuracy. Even the characteristic displacement plateau, which vanishes at higher discharge rates, can be represented. The plateau corresponds to the graphite staging behavior. The effect of the vanishing plateau with higher discharge rates is ascribed to concentration gradients within the graphite electrode. This observation is verified by investigating the displacement relaxation after a constant current discharge at 2C for 1200 s.